High gene flows promote close genetic relationship among fine-wool sheep populations (Ovis aries) in China - Ji-long HAN; Min YANG; Ting-ting GUO; Jian-bin LIU; Chun-e NIU; Chao YUAN; Yao-jing YUE; Bo-hui YANG (Journal of Integrative Agriculture, 2016)
The aim of our present study was to construct genetic structure and relationships among Chinese fine-wool sheep breeds. 46 individuals from 25 breeds or strains were genotyped based on the Illumina Ovine 50K SNP array. Meanwhile, genetic variations among 482 individuals from 9 populations were genotyped with 10 microsatellites. In this study, we found high genetic polymorphisms for the microsatellites, while 7 loci in the Chinese superfine Merino strain (Xinjiang types) (CMS) and 5 loci in Gansu alpine superfine-wool sheep strain (GSS) groups were found deviated from Hardy-Weinberg equilibrium (HWE). Genetic drift FST=0.019 (P<0.001) and high gene flows were detected in all the 7 fine-wool sheep populations. Phylogenetic analysis showed fine-wool sheep populations were clustered in a group independent from the Chinese indigenous breeds such that the 7 fine-wool sheep clustered distinct from Liangshan semifine-wool sheep (LS) and Hu sheep (HY) reflected by different population differentiation analyses. Overall, our findings suggested that all fine-wool sheep populations have close genetic relationship, which is consistent with their breeding progress. These populations, therefore, can be regarded as open-breeding populations with high levels of gene flows. Furthermore, the two superfine-wool strains, viz., CMS and GSS, might be formed by strong artificial selection and with frequent introduction of Australian Merino. Our results can assist in breeding of superfine-wool sheep and provide guidance for the cultivation of new fine-wool sheep breeds with different breeding objectives.